KEWENANGAN PERADILAN AGAMA TERHADAP SENGKETA EKONOMI SYARIAH - Zaida, Yusna (Pascasarjana UIN ANTASARI Banjarmasin, 2007)
A an lslDmic coun in lndonesi4 the Religion Coun has an authority for those. siror religion are klam or those who admit thcir obdience to Islamic laws. lla!.d on I-aw no. 3 / 2006, thero is a new authodty for this instjtution, that is to s.lvc drc dispute on syaria economy or dispute in syaria economic taw. Syaia ccoronl( is lhe Indonesian economc law which is based on svaria. Whreas r.1,,nes,an Economic law is atl rutes and taw decision which sp;ificaly arra.nge rhc ccononric acliviries. The potential eme.ging of dispute in syada economy is relarcd with contract (agreement) in syaria economy thst has familia. term akad, or dispulc of interests between lulancial iNtttution and the filnd usen- or can ,.,r